Implementasi Hybrid Learning Pada Pembelajaran Ekonomi Untuk Menanamkan Nilai-Nilai Pancasila di SMA Negeri 1 Pare - Syahrul Munir; Indra Setyowati (Jurusan Ekonomi Pembangunan Fakultas Ekonomi Universitas Negeri Malang, 2022)
Since the Covid-19 pandemic hit Indonesia, the learning system at all levels of education in Indonesia has shifted from a face-to-face system to an online system. Various problems arise from this system change, ranging from uneven ownership of facilities, difficulty in accessing the internet, boring learning models, and even difficulties in understanding the material. This is what underlies learning that must be done in a hybrid way, especially in economics learning. This is because Economics learning is related to how to fulfill individual and group economic needs. In Economic Education it is also necessary to inculcate the values of Pancasila, because the values of Pancasila will provide a strong ideological foundation in carrying out wise economic activities. The purpose of this study was to describe the implementation of Hybrid learning in SMA Negeri 1 Pare in Economics by instilling the values of Pancasila. This research is a qualitative research. Informants in this study were Economics Teachers and Students at SMAN 1 Pare. Data collection was obtained through field surveys, observations, in-depth interviews with related parties. The results of the study show that in order to minimize problems with the offline system, SMA Negeri 1 Pare implements Hybrid Economics learning. During limited face-to-face learning (PTMT), educators are emphasized to choose interesting Economics learning materials and media to increase students' interest in learning. Various adjustments to the material and lesson plans were made to make it easier for students to understand the material. In addition, the inculcation of Pancasila values in Economics learning is also carried out through 1) Integration of Economic materials with Economic values; 2) Giving examples in everyday life that are of value to Panasila; 3) Giving assignments with the value of Pancasila; 4) Embedding illustrations containing Pancasila values through Economics learning materials and media. DOI: https://dx.doi.org/10.17977/UM014v15i12022p074